ESTIMATION OF UNCERTAINTY IN MEASUREMENT OF DOSE EQUIVALENT AT LABORATORY LEVEL USING CASO4 :Dy-BASED TLD BADGE SYSTEM IN INDIA. Issue 2 (11th December 2019) - Pradhan, S M; Datta, D; Pathan, Munir S; Srivastava, Kshama; Selvam, T Palani
Abstract: The objective of this paper is to estimate the combined uncertainty in the measurement of dose equivalent at laboratory level using CaSO4 :Dy-based thermoluminescent dosemeter badge system by including variations in the components of the system. The variability of performance of the system is analysed using random effects one way analysis of variance model. The model enables estimation of the overall variance of the performance of the sampled population. The population in the study comprises all possible indicated dose equivalents on irradiation of dosemeters to a specific dose equivalent and radiation quality. Coefficient of variation and combined uncertainty at 95% level of confidence in the measurement of H p(10) due to S-Cs radiation quality are found to be 6.6 and 14.3%, respectively, at the dose level of 5.31 mSv. The above parameters in the measurement of in-use quantity, i.e. whole body dose or photon dose equivalent are found to be 7.4 and 16.4%, respectively. The performance of the monitoring system on relative response has been observed to be satisfactory. Various factors affecting the variability of performance of the system are identified for further improvement in coefficient of variation.